Carbohydrates – a scoping review for Nordic Nutrition Recommendations 2023 - Emily Sonestedt; Nina Cecilie Øverby (Food & Nutrition Research, 2023)
Background: Dietary carbohydrates are a major source of energy in the Nordic and Baltic countries. The health effects of different types of carbohydrates vary and there is a need to update the evidence regarding specific carbohydrates and their effects on health-related outcomes. Objective: The aim of this scoping review was to describe the evidence for the role of total carbohydrates (fiber excluded), glycemic index (GI) or glycemic load (GL) and added or free sugars for health-related outcomes as a basis for setting and updating dietary reference values for the Nordic Nutrition Recommendation (NNR) 2023. Method: We included evidence from several qualified systematic reviews (the World Cancer Research Fund, the European Food Safety Authority, the World Health Organization, the United States Dietary Guidelines Advisory Committee, the United Kingdom Scientific Advisory Committee on Nutrition) identified by the NNR project in line with the protocol description. Results: There is limited evidence that total carbohydrate intake (fiber excluded) outside of the current recommended range of 45–60% of energy is associated with health-related outcomes. There were no consistent benefits on clinical outcomes when changing the GI of a diet. High intake of dietary sugars is well known to be associated with dental caries. There was evidence from randomized control trials on surrogate disease endpoints, for a positive and causal relationship between the intake of added and free sugars and risk of some chronic metabolic diseases with moderate level of certainty for obesity and dyslipidaemia. The level of certainty was high for an association between high intake of sugar-sweetened beverages and risk of several chronic metabolic diseases. Conclusion: While there is limited evidence that total carbohydrates and GI and GL of the diet are related to health outcomes, the evidence suggests that high intakes of added and free sugars are related to detrimental health effects. In addition, with increasing intake of added and free sugars, there is less room for healthy foods and micronutrients, which is especially important for those with low energy intake, such as children.